Trajectory Planning and Tracking Control for 6-DOF Yaskawa Manipulator based on Differential Inverse Kinematics - Khoat, Ngo Xuan; Hoa, Cao Thanh Vinh; Khoa, Nguyen Bui Nguyen; Dung, Ngo Manh (Journal of Robotics and Control (JRC), 2024)
In the realm of robotics research, there is a strong focus on trajectory planning and control, driven by the increasing need to integrate robots across diverse industries. Drawing on the traditional Artificial Potential Field (for short, APF) method for path planning, the author proposes modifications on the force field calculation functions and time coefficients. These proposed functions improve the robot arm’s movement to better interact with identified obstacles, regardless of distance conditions. This will help reduce calculation time compared to traditional methods. The research aims to enhance the operational system of the manipulator by developing an external program that interfaces with the central controller. The program guides the robot arm to follow a specific path using the Differential Inverse Kinematics (for short, DIK) method to ensure the smoothness of trajectory tracking. Facing the issue of the invertibility of the Jacobian matrix, the research team addressed it by adding a Moore–Penrose right pseudoinverse of the Jacobian and avoiding the shock velocity around the singularity using a Damping Constant technique. In this research, the proposed APF is validated and compared to the traditional method using MATLAB. The DIK method utilizes the optimal path from previous to control the Yaskawa MotoMINI manipulator - the physical robot arm system.